Digitalisasi Budaya Politik Melalui Peran Generasi Milenial dan Gen Z Di Indonesia - Sion Hutajulu; Stiven Ginting; Yehezkiel Manasyekh (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In this paper, the digitalization of politics is discussed through the role of millennials and Gen Z in Indonesia. Millennials and Gen Z can utilize social media and technology to voice their opinions, raise political awareness, and actively participate in the democratic process. For example, they can organize social actions or conduct political campaigns through internet platforms in the political context, spreading boaxes has become easier and faster thanks to advances in technology and social media. As a result, there needs to be an effort to solve this problem. Improving digital literacy and educating people on how to find and verify information. Before sharing are steps that can be taken. In addition, the government, educational institutions and the media should be active in combating the spread of houxes. .